Biobased Vanillin Production by Oxidative Depolymerization of Kraft Lignin on a Nitrogen- and Phosphorus-Functionalized Activated Carbon Catalyst - García-Rollán, Miguel; Rivas-Márquez, María Nerea; Bertran-Llorens, Salvador; Deuss, Peter J.; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (ACS, 2024)
The sustainable production of vanillin from the oxidative depolymerization of lignin was evaluated. Vanillin was produced from Kraft lignin using heterogeneous catalysts based on activated carbons prepared by chemical activation of sodium lignosulfonate with H3PO4. The novel redox catalytic system, obtained by HNO3 treatment, allows the heterogenization of nitrobenzene structures on the activated carbon, reaching vanillin yield 30% higher than that obtained without a heterogeneous catalyst (about 3.1 wt %). A copper catalyst (5 wt %) was also prepared for comparison purposes. The highest vanillin yield was obtained at 200 °C and 10 bar for the nitrobenzene-like catalyst, reaching full extraction from the selected technical lignin. The catalyst was successfully reused without any regeneration treatment, evidencing no signs of deactivation. The possibility of transferring oxygen from oxidized P groups to reduced N groups in a redox cycle seems to be responsible for this sustained catalytic activity. To promote zero waste production, the obtained residual lignin was also used to prepare an activated carbon with outstanding properties, ABET ∼ 1000 m2/g.
Keywords: Biopolímeros; Catalizadores; Polímeros - Degradación; Biopolymers; Carbon; Catalysts; Depolymerization; Organic polymers